An overview of Chinese and Indonesian adjective predicate to deepen understanding and translation - Trihardini, Ayu (International Journal of Culture and Art Studies, 2025)
Predicates are considered the center of sentences, and understanding them will help students understand the meaning of various utterances. A contrastive study between languages helps to understand the target language being studied. However, research on the contrast of Chinese and Indonesian predicates has not received enough attention. This paper focuses on a contrastive analysis of Chinese and Indonesian adjective-predicate sentences, namely the syntactic units that form the predicate and the related grammatical rules. The data in this study were Chinese and Indonesian adjective-predicate sentences from short stories, novels, and associated grammatical works. The data obtained were then analysed using the procedure described by James and the contrastive analysis method by Di Pietro. The results of the study show that Chinese and Indonesian predicates are similar in definition, but differ in the internal structure. The fundamental difference is that bare adjectives in Chinese sentences are used only in comparative contexts. In addition, some Indonesian adjective-predicate sentences must be added with “adalah” or demonstrative pronouns between the subject and predicate. While the equivalent in Mandarin is the verb “shi”, and sentences whose predicates are added with verbs will become verbal sentences. These findings will undoubtedly contribute to the understanding of Chinese language learners from Indonesia and are expected to provide input and references in the field of translation.